SOME FUNCTIONS RELATED TO Š α∗ - OPEN SET IN SOFT TOPOLOGICAL SPACES (International Journal of Food and Nutritional Sciences, 2022)
In this paper, we introduce some soft functions like Š Perfectly ????∗ - continuousfunction, Š Totally ????∗ - continuous function. We study the connections of these function withother Š function . Also, we establish the relationships in between the above functions and alsoinvestigate various aspects of these functions.